Isolation of endophytic bacteria from the roots of Gliricidia sepium and their ability as IAA-producing bacteria and phosphate solubilizers - Nurul Rizqiyah; Lalu Zulkifli; Agus Ramdani (Jurnal Biologi Tropis, 2022)
This study aimed to isolate endophytic bacteria from the roots of the gamal plant and to test its ability to solubilize anorganic phosphate dan to produce IAA (indol acetic acid). The steps in this study were the isolation of endophytic bacteria from the roots of the gamal plant taken from Woja District, Dompu Regency, the IAA test, and the phosphate solubility test using the colorimetric method. And then carried out the characterization of cells, colonies and biochemical properties of isolates. In this study, 6 isolates of endophytic bacteria from the roots of gamal plants were obtained which can dissolve phosphate, of which two isolates, namely ATG1 and ATG4 with phosphate solubility indices ranging from 3 and 4. These two isolates were also capable of producing IAA, with concentrations 16.48 and 17.72 ppm, respectively. Most of the isolates were Gram positive bacteria and were in the form of bacilli. The endophytic isolates obtained above are isolates that have the potential to be candidates for components of the biofertilizer formulation consortium in the future.